Оптимальное распределение задач управления по компонентам базовой компьютерной сети системы управления объектом критического применения - Кучук, Г. А.; Коваленко, А. А. (ХНУРЭ, 2014)
The paper discusses approaches to a stage of critical application object control system’s that is logically inseparable with computer system’s technical structure synthesis and that consists of distribution, in optimal way, control tasks among the components of computer system. The main stages, as well as appropriate tasks that should be solved, are marked out, described and formalized
Keywords: распределение задач управления; компоненты базовой компьютерной сети; система управления объектом